Исследование индуктивной синергетической системы автоматического управления процессом флотации углей - Зубов, Д.А.; Килымник, О.В. (Міжнародний науково-навчальний центр інформаційних технологій і систем НАН та МОН України, 2009)
In this paper, new approach of inductive synergetic synthesis of nonlinear aggregated regulators is proposed on the basis of A.A.Kolesnikov synergetic control theory and A.G.Ivakhnenko selforganizing systems (with the coal flotation process application). Selection of attracting invariant variety (IV) is carried out on the structure parametric IV synthesis basis in the context of selforganizing systems. Procedure of inductive synergetic synthesis of nonlinear aggregated regulators can be described through the record with next arguments: set of the nonlinear aggregated regulators synergetic synthesis methods; ranged set of the IV selection criterions; set of IV structures; set of IV generation algorithms on the IV structures basis; set of rules for the IV selection criterions complexing.